Detection of sybil attacks based on periodic ultra wide band distance information in WSN - Yanzhi ZHANG; Xiaoqin YE (Dianxin kexue)
Concerning the problem that wireless sensor network is vulnerable to many kinds of network attacks and compromise of nodes，a complete detecting system of sybil attack based on periodic ultra-bandwidth distance information was proposed.Firstly，the distance between the adjacent nodes was ranging and the hello data packet was exchanged.Then，the distance estimation form was constructed by local estimation，and the form was contained in each node.Meanwhile，multiple distance matching check was periodically executed for each node in the network.Finally，when there was the distance matching between the legitimate node at least two different nodes，it would give an alarm and discard the sybil nodes.If there was no distance matching，the node continued normal operations.IEEE 802.15.4 peer to peer sensor networks were adopted in the simulation experiments.Experimental results show that the proposed system not only can tolerate changes in the number of complicated sybil attacks，but also can successfully deal with the occurrence of complicated，malleable sybil attack.In addition，the probability of false alarm is very small，the entire network performance and its consistency are not affected.